PEMBINAAN PROGRAM USAHA PENINGKATAN PENDAPATAN KELUARGA SEJAHTERA (UPPKS) DI KECAMATAN LUBUK SIKAPING KABUPATEN PASAMAN - Jerri Adam; Zulkarnaini " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Coaching is an effort, action and activity carried out in an efficient manner to obtain better result, While the (UPPKS) program is a program formed by the government aimed at women who participate in family planning with various stages of a prosperious family that is prioritized to those who are less able to meet the needs in their families.so that they are given coaching to carry out business through the formation groups until they are independent in entrepreneurship or meet the economic needs of their families.this study aims to find out how and factors that influence the  business program to increase the income of a prosperious family in lubuk sikaping subdistrict, pasaman regency.researches used a qualitative descriptive approach using a purposive sampling methods with data collection techniques using interview, observasion, and documentation.the theoretical concept used is the concept of coaching implementation according to santoso, namely the provision of guidance, provision of forums, education or training and field checking including influencing factors. The result of this study can be seen that the UPPKS group coaching is carried out by the population control and family planning (DPPKB) pasaman regency is not yet optimal, the factors that influence the implementation of this guidance are human resources , budget and business acces. Keywords: Coaching, UPPKS Program.